Infestation of Two Bostrichid Stem Borers on Neem Tree (Azadirachta indica A. JUSS.) - First Report from Indian Thar Desert: INFESTATION OF BOSTRICHID STEM BORERS IN NEEM: FIRST REPORT - Richhpal Singh,; Sreedevi, Kolla; Narpat Singh Shekhawat, (Annals of Arid Zone, 2024)
Neem (Azadirachta indica A. Juss.) trees are infested by two powder post stem borers (Coleoptera; Bostrichidae) at Luni (Marwar), Jodhpur, Rajasthan. The powder post stem borers (beetles) attack juvenile and young branches of 5-7-years-old neem trees. The infested trees exhibit severe dieback syndrome, dry and die. The two neem beetle pests are identified as species of Amphicerus and Sinoxylon. Mode, and patterns of feeding and infestation are studied. Process of tree mortalities are recorded. It is first report on dual attack of insect pest menace to neem tree which is a major source of bioactive molecule azadirachtin and ecosystem services of the fragile ecosystems